COVID‐19 in Parkinson’s Disease Patients Living in Lombardy, Italy - Fasano, Alfonso (Mov Disord, 2020)
BACKGROUND: It is unknown whether patients with PD are at greater risk of COVID‐19, what their risk factors are, and whether their clinical manifestations differ from the general population. OBJECTIVES: The study aimed to address all these issues. METHODS: In a case‐controlled survey, we interviewed 1,486 PD patients attending a single tertiary center in Lombardy, Italy and 1,207 family members (controls). RESULTS: One hundred five (7.1%) and 92 controls (7.6%) were identified as COVID‐19 cases. COVID‐19 patients were younger, more likely to suffer from chronic obstructive pulmonary disease, to be obese, and vitamin D nonsupplemented than unaffected patients. Six patients (5.7%) and 7 family members (7.6%) died from COVID‐19. Patients were less likely to report shortness of breath and require hospitalization. CONCLUSIONS: In an unselected large cohort of nonadvanced PD patients, COVID‐19 risk and mortality did not differ from the general population, but symptoms appeared to be milder. The possible protective role of vitamin D supplementation warrants future studies. © 2020 International Parkinson and Movement Disorder Society